Trade reserve and exchange rate: a comparative analysis of high, moderate, and low trade openness countries - Suleman, Shahida; Mohd Thas Thaker, Hassanudin; Cheong, Calvin Wing Hoh (Routledge, 2025)
This study aims to comprehensively examine the impact of trade reserves (TR) on exchange rates (ER) across different degrees of openness economies – specifically high, moderate, and low openness – from 1997 to 2020. Utilizing advanced panel regression techniques, the research assesses long-term dynamics through Pedroni cointegration and explores causal relationships via Granger causality tests. The findings indicate both long-term and short-term relationships between TR and ER. Notably, the study reveals a significant inverse effect of TR on ER, with the impact of trade on ER being particularly pronounced in low-openness economies.